2022
DOI: 10.1186/s12884-022-05037-8
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of early essential newborn care on breastfeeding and maternal outcomes: a nonrandomized controlled study

Abstract: Background Breastfeeding and maternal health play crucial roles in improving newborn health, which is closely related to the development of families and society. Early essential newborn care, which emphasizes early exclusive breastfeeding and skin-to-skin contact, is recommended by the World Health Organization. This study aimed to explore the association of early essential newborn care with breastfeeding and maternal outcomes. Methods A nonrandomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
0
9
0
1
Order By: Relevance
“…anxiety. 32 A systematic review reported that in the case of immediate, intraoperative skin-to-skin contact, maternal stress levels were reduced, whereas comfort, oxytocin and antioxidant levels increased. 33 The safety of skin-to-skin contact immediately after birth has been questioned.…”
Section: Key Notesmentioning
confidence: 99%
See 4 more Smart Citations
“…anxiety. 32 A systematic review reported that in the case of immediate, intraoperative skin-to-skin contact, maternal stress levels were reduced, whereas comfort, oxytocin and antioxidant levels increased. 33 The safety of skin-to-skin contact immediately after birth has been questioned.…”
Section: Key Notesmentioning
confidence: 99%
“…63 When combined with EENC both the duration of the third stage of labour and blood loss have been shown to decrease. 32 A 2003 systematic review of 7 RCTs which evaluated the effect of mother/baby skin-to-skin care on successful breastfeeding reported that the evidence 'failed to support the current initiatives to implement changes in clinical practice to include skin-to-skin contact'. 64 However, a later review, published by the Cochrane Database of Systematic Reviews, included 38 studies and reported that 'the evidence from this updated review supports using immediate or early SSC (skin-to-skin contact) to promote breastfeeding'.…”
Section: Key Notesmentioning
confidence: 99%
See 3 more Smart Citations